Recuperación de la cartera vencida y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito San Antonio ltda. Los ríos. Agencia San Carlos período 2021-2022. - Carbo Castro, Karen Geovanna (2024)
The overdue portfolio is one of the most important problems that Financial Institutions currently face. The inability of partners to pay their loans on time can generate significant losses, since its recovery allows eliminating the risk of business bankruptcy due to lack of timely collection of the credits granted. That is why the objective of this investigation is to evaluate the recovery of the overdue portfolio of the Cooperativa de Ahorro y Crédito San Antonio Ltda. Agencia San Carlos, and its impact on profitability, due to the existing problems in this Institution where It shows deficiencies and weaknesses in the application of policies in the processes of credit placement, collection management, judicial and extrajudicial processes, affecting profitability indicators, the increase in the delinquency rate and the provision of the portfolio. Inductive and deductive research methods were used to obtain the results and understand the factors that caused its deterioration. Likewise, instruments were used that served to develop the research, such as the interview applied to the Head of the Agency of the Cooperative, the evaluation of credit and collection policies, through which the reality of the financial institution was known, a Once the instruments were applied, the results of the research were obtained, based on this the conclusions and recommendations will be presented.